Isolation and Identification of Arbuscula Mycorrhiza (Ma) in Plant Rhizosphere in Greenbelt Area of PT. Semen Indonesia Tbk Tuban - Avivi Nur Aina; Supiana Dian Nurtjahyani; Sriwulan Sriwulan; Eko Purnomo (Journal of Biodiversity and Biotechnology, 2023)
The Green Belt area is a buffer area in an industrial area that functions as a barrier or separates the mining area from other regions, such as residential areas or community agriculture. The Green belt area consists of various plant vegetation that absorbs carbon dioxide and air conditioning, preventing sedimentation and erosion in the mining area. Arbuscular mycorrhiza has the potential to live in the green belt area by forming a mutualism symbiosis with plants or vegetation in the area. This study aimed to determine arbuscular mycorrhizae found in the Greenbelt area of PT Semen Indonesia Tbk Tuban. Sampling used purposive sampling techniques at three sampling stations, namely rhizosphere eucalyptus (Malaleuca cajuputi), trembesi (Samanea saman), and sawo (Manilkara zapota). The study was conducted in November 2021 through three stages: sampling, sample isolation, and species identification. The results showed seven types of arbuscular mycorrhiza from five different genera, namely the genus Glomus, Acaulospora, Gigaspora, Racocetra, and Archaeospora. The most found species is the genus Glomus. This research contributes as a source of literacy and information about the types of AMF found in PT Semen Indonesia's Greenbelt area, which can be used as biological fertilizer, support plant growth, help reclaim mining areas, and protect plants from drought pressure in mining areas.